2017
DOI: 10.4236/jbm.2017.57006
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Effect of Germanium or Germanium Compounds on Animals—A Review

Abstract: An increasing number of researches have been focused on the relationship between trace elements and animal health. Germanium, as a widely used trace element, exists ubiquitously as germanium or germanium compounds in the living environment of human and animals, and plays important roles in animal production or health. With the intensive study of the physiological function of germanium and its compounds, the effects of germanium on animal physiological functions and health have been gradually confirmed. In this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
15

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 45 publications
0
11
0
15
Order By: Relevance
“…In humans, inorganic forms of Ge (Ge in ) are associated with toxicity. Experimental models have shown that its organic forms (Ge org ) may in turn display antioxidant, immunomodulatory and anticancer properties although the use of Ge-containing supplements is currently disregarded [20].…”
Section: Introductionmentioning
confidence: 99%
“…In humans, inorganic forms of Ge (Ge in ) are associated with toxicity. Experimental models have shown that its organic forms (Ge org ) may in turn display antioxidant, immunomodulatory and anticancer properties although the use of Ge-containing supplements is currently disregarded [20].…”
Section: Introductionmentioning
confidence: 99%
“…Серед таких нанопрепаратів особливий статус належить цитрату германію (Ge), що має імуностимулюючі, протизапальні та антиоксидантні властивості, забезпечує зниження гіпоксії на тканинному рівні. Показано його стимулюючий вплив на імунобіологічну реактивність та репродуктивну функцію щурів [4][5][6]. Також випоювання цитратом Ge сприяло покращенню імунобіологічних показників щурів, в тому числі їх фертильності і молочності самиць [4,7,8].…”
Section: вступunclassified
“…These interactions have been ¿ rmly established for most macro-and trace elements, and they are normalized in nutrition [1][2][3]. The regulatory impact of physiologically active, but insuf¿ ciently studied elements, among which germanium takes a prominent place, on organtissue distribution of other minerals, is presently actively studied in biology, medicine, and veterinary science [3,4]. Organic formulations of macro-and trace elements (nanoaquachelates) as obtained by nanotechnology methods receive special attention [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, our earlier research [7,8] showed that the administration of germanium citrate, obtained via the erosive and explosive ablation with electro-impulse, caused a number of biological effects in the organism of rats. This may have found its cause in the fact that germanium (Ge) has an immuno-stimulating effect, enhances transport and transfer of Ɉ 2 and ensures the decrease of hypoxia at tissue level [3,4]. Certain organic forms of Ge have negatively charged oxygen ions that can scavenge free damaging hydrogen ions and minimize their damage to cells and tissues [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation